FAKTOR DETERMINAN KEMAMPULABAAN SAHAM BLUE CHIP DI BURSA EFEK INDONESIA - Dyah Ayu Widiastuti; Beta Asteria (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2019)
The company runs its business to make a profit. The company’s ability to earn profits with assets owned is called profitability. This study aims to analyze the factors that affect the profitability of Blue Chip Shares. These factors are Debt to Equity Ratio (DER), Firm Size which is proxied by Total Assets, and Price to Book Value. The research model uses multiple regression analysis. During the year of observation of 45 Blue Chip stocks that entered into the PurposiveSampling there were 36 companies in 2014 to 2017, so the study sample was 144. The results of the study proved that partially Debt to Equity Ratio (DER) and Price to Book Value to Blue stock profitability Chip. While Firm Size partially has no significant effect on Blue Chip stock profitability. As well as Debt to Equity Ratio (DER), Firm Size which is proxied by Total Assets, and Price to Book Value significantly influence the profitability of Blue Chip shares simultaneously.